﻿RACIAL DISCRIMINATION OF LOVE IN GUESS WHO MOVIE (2005) DIRECTED BY KEVIN RODNEY SULLIVAN: A SOCIOLOGICAL APPROACH - RAKASIWI, RIRIS (2010)
This research paper elaborates the discrimination in Kevin Rodney Sullivan's Guess Who movie that is analyzed through a sociological approach. The objectives of the research are to analyze the structural elements of the movie and to analyze the movie based on a sociological approach. This research belongs to a descriptive qualitative research. The data of the research is the movie entitled Guess Who. Whereas the data source comes from both primary data source which is in the form of the text of the movie being researched and secondary data source such as biography of the author, websites and other sources. The method to analyze the data is descriptive analysis. Based on the analysis toward the film, the writer concludes that the discrimination of love are shown by the structural elements which build the film such as characters, setting, plot, theme, and mise-en-scene and from sociological aspects : those are from social aspect, political aspect, economic aspect, cultural aspect, and religious aspect. The writer also finds that the director uses the great events influencing America to support the theme of the film and to support the discrimination of love shown in this film. From the sociological aspects shown in the film, the writer then concludes that literary work reflects certain age when it is made, dealing with the social situation of the authors, and as manifestation from the historical moment.